COMPARISON OF ISLAMIC BANKS PERFORMANCE AND CONVENTIONAL BANKS PERFORMANCE IN MUSLIM-MAJORITY PROVINCES AND NON-MUSLIM MAJORITY PROVINCES - Eko Fajar Cahyono; M. Fariz Fadillah Mardianto; Tika Widiastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri (UIN), 2020)
This study aims to look a universality services Islāmic banking and conventional bank services and products in Indonesia by testing whether the services and products of conventional Islāmic banks and conventional banks accepted by all groups, both Muslims and non-Muslims. The method used was the Multivariate Analysis of Variance (MANOVA) test by comparing Islāmic banks performance and conventional banks performance represented by several financial ratios in a number of provinces in Indonesia. There are two provincial categories, namely the first group is a provincial province with a most Muslim population and the second is a class of provincial provinces with a most non-Muslim population in Indonesia.